E-Commerce development and household consumption growth in China - Luo, Xubei; Wang, Yue; Zhang, Xiaobo (World Bank, 2019)
China has quickly become the largest e-commerce market in the world. By matching a nationally representative China Family Panel Studies survey with county-level e-commerce information obtained from Alibaba, this paper examines how e-commerce development has shaped household consumption growth in China. The paper presents three major findings. First, e-commerce development is associated with higher consumption growth. Second, the relationship is stronger for the rural sample, inland regions, and poor households, suggesting that e-commerce development helps reduce spatial inequality in consumption. Third, the consumption of durable goods and in-style goods has grown faster than the consumption of local services.